Grade-Free Learning System as A Means of Creating a Psychologically Comfortable Educational Environment in the Class to Motivate a Child to Successful Learning Activities (Eurasian Research Bulletin, 2022)
In modern elementary school, the problem of ungraded education is very relevant. The main encouragement and the strongest (but not always effective) punishment in pedagogical work is assessment. This is a tool that the teacher must be able to use.